Perception of Internet Use in Relation to Health Decision-Making among Nursing Students - José A. Zafra-Agea; Noelia Calvillo-Nuñez; Òscar Gil-Jiménez; Ivan Hellín-Pijuan (MDPI AG, 2023)
Internet use has increased worldwide during the COVID-19 pandemic, to the point where it has inadvertently integrated into our lives. University students use the Internet daily for different purposes: seeking information, entertaining, as a teaching and learning tool, they consider social networks as a means of connection and social interaction, and to seek information to make health decisions. Because of this, the Internet and social networks have gained popularity among this group, to the point of developing an abusive use that is not perceived as an addictive risk. A descriptive analysis was performed through the adaptation of a survey about Internet use, social networks and health perception; this survey was given to nursing students of the Gimbernat School during the academic year 2021-2022. Students completed the ad hoc questionnaire (N = 486; 83.5% female, 16.3% male; only 1 declared to be non-binary gender). Our hypothesis had to do with whether the population of nursing students at Gimbernat School had increased, after the pandemic, its use of the Internet and social networks to make decisions about health problems. The objective of the study was to analyse differences in students' habits of use of the Internet and social networks as they look for health information, their decision-making when they find the information and their perception of health as nursing students from a gender perspective. The results showed a clear positive relationship between the variables studied. Of nursing students, 60.4% spend between 20 and more than 40 h a week using the Internet, and 43.6% of these hours are spent on social networks. Of students, 31.1% make health decisions by searching for information on the Internet and consider it useful and relevant. The use of the Internet and social media in relation to health decisions is clearly affected. To try to reduce the incidence of the problem, interventions are needed regarding the prevention and/or consequences of Internet abuse and health education of student nurses as future health assets.